CAMPURSARI ALA DIDI KEMPOT: PEREMPUAN DAN LAKI LAKI JAWA MENDOBRAK PATRIARKI - Damayanti Gani1 dan Willy Chandra, Yola (Institute of Research and Community Outreach - Petra Christian University, 2007)
The research was embarked from the researcher interest in phenomenon of campursari new Javanese ethnic music which around 2000 was popularized by Didi Kempot origin of Solo%2C Central Java. Songs of Campursari texts in study analysis of Semiotics had laden with social codes that could describe Javanese women and men. Originated from cultural stereotype%2C Didi Kemp not only represented Javanese men who were calm and did not like conflicts%2C yet he also presented Javanese men (just like women) also prioritized feeling. Still under cultural umbrella of Patriarchy%2C women strove to break down patriarchal ideology that overshadowed them. Through his songs%2C Javanese women were depicted more courageous in determining their attitudes. Abstract in Bahasa Indonesia : depiction%2C text%2C javanese culture%2C patriarchy